Relationship Between Lipid Peroxidation and Vitamine (E) , ï¡ -Tocooherol Supplementation in Sera of Apparntly Healthy Individuals - Al-Mashhadani, Z.I.; Al-Baityi, A.; Al-Zubadyi, L.S (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
In an attempt to shed a light on the possible relationship between lipid peroxidation and some antioxidant. The effect of vitamine E (as a potent antioxidant free radical scavenger) on the serum levels of Total cholesterol (TC) and Triacylglycerols (TG) was studied and the lipid peroxidation marker (MDA) was measured. The study includes (50) healthy donors from males and females who had given vitamine E at a rate of (400IU) daily for one month and were divided into two groups. 1. Group (A) : included (25) males donors (20-40) years old, before and after giving vitamine E. 2. Group (B) : included (25) females donors (20-40) years old , before and after giving vitamine E. The result of the study indicated and confirmed the role of Vitamine E in reducing the lipid peroxidation marker serum MDA in the studied groups. (TC) and T(G) levels were reduced after supplementation with Vitamin E in sera of apparently healthy donors.